PRO-VAS: utilizing AR and VSLAM for mobile apps development in visualizing objects - Sofianita Mutalib; Mohd Alif Izhar; Shuzlina Abdul-Rahman; Mohd Zaki Zakaria; Mastura Hanafiah (Universitas Ahmad Dahlan, 2022)
The development of mobile apps with augmented reality (AR) would enhance the capability in visualizing the scene or environment. Any apps supported by computer aided design versions with 3D models makes the design more realistic, such as in the form of websites or mobile apps. However, the current features for online platforms for shopping are quite limited and lack 3D visualization features. This paper presents the development of a mobile application, pro-visualizer app called PRO-VAS, that utilizes AR for scanning and visualizing the environment. PRO-VAS acts as a product visualizer that applies visual simultaneous localization and mapping (VSLAM) for localization of the product in AR based systems. The main components of PRO-VAS are ARCore from Google for interactive purposes, and the depth mapping from red green blue depth (RGB-D) phone camera with point plane generator and markerless tracking method. The last component of the app is the set of objects from the unity store, which can be chosen in PRO-VAS for the scanned scene area. The app was tested in various environments involving different objects and has shown competitive results. In the future, more features and products can be added to the apps.